Difficult People: Who Is Perceived to Be Demanding in Personal Networks and Why Are They There?. Issue 1 (February 2018) - Offer, Shira; Fischer, Claude S.
Why do people maintain ties with individuals whom they find difficult? Standard network theories imply that such alters are avoided or dropped. Drawing on a survey of over 1, 100 diverse respondents who described over 12, 000 relationships, we examined which among those ties respondents nominated as a person whom they "sometimes find demanding or difficult." Those so listed composed about 15 percent of all alters in the network. After holding ego and alter traits constant, close kin, especially women relatives and aging parents, were especially likely to be named as difficult alters. Non-kin described as friends were less likely, and those described as co-workers more likely, to be listed only as difficult alters. These results suggest that normative and institutional constraints may force people to retain difficult and demanding alters in their networks. We also found that providing support to alters, but not receiving support from those alters, was a major source of difficulty in these relationships. Furthermore, the felt burden of providing support was not attenuated by receiving assistance, suggesting that alters involved in reciprocated exchanges were not less often labeled difficult than were those in unreciprocated ones. This study underlines the importance of constraints in personal networks.